The Troll Inside You: Paranormal Activity in the Medieval North - Ármann Jakobsson, 1970- (Book collections on Project MUSE., 2017)
What do medieval Icelanders mean when they say "troll"? What did they see when they saw a troll? What did the troll signify to them? And why did they see them? The principal subject of this book is the Norse idea of the troll, which the author uses to engage with the larger topic of paranormal experiences in the medieval North. The texts under study are from 13th-, 14th-, and 15th-century Iceland. The focus of the book is on the ways in which paranormal experiences are related and defined in these texts and how those definitions have framed and continue to frame scholarly interpretations of the paranormal. The book is partitioned into numerous brief chapters, each with its own theme. In each case the author is not the least concerned with how the paranormal functions within medieval society and in the minds of the individuals who encounter and experience it and go on to narrate these experiences through intermediaries. The author connects the paranormal encounter closely with fears and these fears are intertwined with various aspects of the human experience, including gender, family ties, and death. The Troll Inside You hovers over the boundaries of scholarship and literature. Its aim is to prick and provoke but above all to challenge its audience to reconsider some of their preconceived ideas about the medieval past.